Determinants of individual healthcare expenditure: a cross-sectional analysis in rural Burkina Faso - Nakovics, Meike Irene; Brenner, Stephan; Robyn, Paul Jacob; Tapsoba, Ludovic Deo Gracias; De Allegri, Manuela (The international journal of health planning and management, 2019)
Introduction Overwhelming evidence suggests that out-of-pocket expenditures (OOPEs) hamper access to care and impose a heavy economic burden across sub-Saharan Africa (SSA). Still, current user fee reduction and removal policies often target specific groups and services, leaving large sections of the population exposed to OOPE. Methods To estimate the magnitude and the determinants of OOPE for curative services in Burkina Faso, we used data from a household survey conducted in 24 districts between October 2013 and March 2014 (n = 7844). Given a context of medical pluralism, we purposely focused on total OOPE irrespective of type of care sought. We used a two-part regression model to estimate determinants of OOPE. Results Nearly 60% of those who reported an illness episode incurred a positive expenditure, with an average amount of 9362.52 FRS CFA per episode (1 USD = 577.94 FRS CFA). The first model revealed that the probability of incurring a positive OOPE was positively associated with perceived illness severity (P < .001), hospitalization (P < .001), and negatively associated with age (P = .026), distance (P = .060), and poorest wealth quintile (P = .054). The second model revealed that the magnitude of OOPE was positively associated with age (P = .087), education (P = .025), being household head (P = .015), having a chronic comorbidity (P = .025), perceived illness severity (P = .029), and hospitalization (P < .001) and negatively associated with symptoms unlikely to lead to adverse outcomes if not attended to in time (P = .056). Conclusion Our findings indicate that OOPEs remain a problem in Burkina Faso and that broader spectrum policy reforms are urgently needed to ensure adequate financial protection.
Gesehen am 31.03.2020